Light-emitting diode photobiomodulation therapy for non-specific low back pain in working nurses: A single-center, double-blind, prospective, randomized controlled trial. Issue 32 (7th August 2020) - Lin, Yen-Po; Su, Ying-Hao; Chin, Shih-Fang; Chou, Yu-Ching; Chia, Wei-Tso
Abstract: Background: Low back pain (LBP) affects approximately 51% to 57% of hospital nurses and nurses' aides in Europe. New high-risk groups include home- and long-term-care nurses and physiotherapists. A number of European countries are experiencing a shortage of healthcare workers. Light therapy has been shown to be an effective treatment for various musculoskeletal disorders, including lateral epicondylitis, temporomandibular joint pain, carpal tunnel syndrome, and delayed-onset muscle soreness. A systematic review and meta-analysis demonstrated that low-level laser therapy is an effective method for relieving non-specific chronic low back pain (NSCLBP). However, the efficacy of light-emitting diode (LED) therapy for NSCLBP is disputed. This study aims to evaluate the effect of LED therapy on NSCLBP. Methods and analysis: We conducted a prospective, double-blind, randomized placebo-controlled trial of 148 patients with NSCLBP. The patients were randomly assigned to 2 groups: intervention group, where patients received LED photobiomodulation therapy 3 times a week for 2 weeks, and the sham group, where patients had sham therapy 3 times a week for 2 weeks. Primary outcome measures included the visual analog scale for pain, lumbar active range of motion assessments, and chair-rising times. Secondary outcome measures included a multidimensional fatigue inventory, fear-avoidance beliefs questionnaire, and the Oswestry disability index. The outcome measures were assessed before therapy and 2weeks, 4 weeks, 8 weeks, 12 weeks, and 6 months after the first interventions were completed. Discussion: This study is a prospective, single-center, double-blind, randomized, controlled study. This study aims to research the efficacy of a 2-week LED program for NSCLBP working nurse. Our results will be useful for patients, working nurses, nurses' aides, and other healthcare workers with chronic low back pain. Trial registration number: NCT04424823